“SETTING AREA” PEDAGANG INFORMAL SEBAGAI PENDUKUNG AKTIVITAS DI KORIDOR JALAN KINTAMANI KOTA BATAM - Helen Cia; Suzanna Ratih Sari; Agung Budi Sardjono (Jurnal Arsitektur ARCADE, 2020)
Abstract: Almost every city and every country, besides having a formal sector also has an informal sector. The emergence of street vendors along the Kintamani corridor is an activity that supports the main activities taking place in the area. The main activities include worship, education, commercial and housing. The existence of street vendors trading activities has led to new activities in this road corridor where in addition to being a vehicle circulation, also a parking lot and even a place to gather and relax especially in the afternoon. Setting area aims to find out, recognize the diversity of street vendors activities and know the space needed by street vendors so that they know the pattern of setting areas that accommodate the diversity needs of street vendors as supporting activities without disturbing the main activities of the Kintamani Road corridor and the surrounding environment. The approach taken is to use a qualitative approach with a descriptive exploratory method. Interview with selected respondents based on certain criteria. Data analysis was performed by classifying the diversity of street vendors in the corridor. This area setting is expected to be able to solve city problems, street vendors themselves as perpetrators who are often evicted or forcibly moved and also the Batam city government as a policy maker so that urban spatial planning is synergized to improve the economy of the community and city.Keyword: Setting area, diversity of informal traders, supporting activity.Abstrak: Hampir setiap kota maupun setiap negara, selain mempunyai sektor formal juga mempunyai sektor informal. Kemunculan PKL di sepanjang koridor jalan Kintamani merupakan aktivitas yang mendukung kegiatan utama yang terjadi di kawasan tersebut. Kegiatan utama tersebut antara lain kegiatan ibadah, pendidikan, komersial dan perumahan. Adanya kegiatan perdagangan PKL ini menimbulkan aktivitas baru di koridor jalan ini dimana selain sebagai sirkulasi kendaraan, juga menjadi tempat parkir bahkan menjadi tempat berkumpul dan santai terutama di sore hari.Setting area bertujuan untuk mengetahui, mengenali keragamanan aktivitas PKL dan mengetahui ruang yang dibutuhkan oleh PKL sehingga mengetahui pola setting area yang mengakomodir kebutuhan keragaman PKL sebagai aktivitas pendukung tanpa mengganggu aktivitas utama dari koridor Jalan Kintamani dan lingkungan sekitar. Pendekatan yang dilakukan adalah menggunakan pendekatan kualitatif dengan metode deskriptif eksploratif. Wawancara pada beberapa responden yang dipilih berdasarkan kriteria tertentu. Analisis data dilakukan dengan melakukan klasifikasi keragaman PKL yang ada di koridor jalan tersebut. Setting area ini diharapkan bisa menyelesaikan permasalahan kota, PKL itu sendiri selaku pelaku yang seringkali digusur atau dipindahkan secara paksa dan juga pihak pemerintah kota Batam selaku pembuat kebijakan sehingga tercapai tata ruang kota yang saling bersinergi untuk meningkatkan perekonomian masyarakat dan kota.Kata Kunci: Setting area, keragaman pedagang informal, pendukung aktivitas